“NEURALINK” Implantation of Artificial Intelligence in Humanbeings - Anjana, MP (International Journal of Computer Sciences and Engineering, 2025)
Intelligence exhibited by machines is known as artificial intelligence. We are all aware of the advantages of AI and how it has proved to be helpful in fields like agriculture, medical diagnosis, electronic training, robotic control and remote sensing. At the same time we may also have to analyze the negative side of artificial intelligence. Artificial Intelligence exceeding humans in reasoning and intelligence can replace humans and take away their jobs. This paper discusses about Ellon Musk’s Neuralink which is centered on creating artificially intelligent devices like brain chips that can be implanted in human brain with purpose of helping humans merge with software and to keep pace with the advancements in artificial intelligence with the help of the Neural Lace Technology. This paper has attempted to give the basic idea of Neural Lace and how this can be helpful in overcoming brain disorders like chronic pain disorder permanently and help the patients get rid of the side effects of the medication of chronic pain disorder that has got several side effects.